CULTIVATION OF FAMILY MEDICINAL PLANTS AND ORGANIC RICE IN PAYU PUTAT VILLAGE, WEST PRABUMULIH SUBDISTRICT, PRABUMULIH CITY - Noviyanti, Fira; Masona, Sarion (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Payu Putat Village, known for its fertile soil and ample land, has excelled in vegetable production, including rice, vegetables, and medicinal plants. Despite these advantages, insufficient agricultural knowledge and management have given rise to environmental challenges, such as floods, surplus harvests leading to waste, and depressed vegetable prices due to oversupply, consequently diminishing farmer incomes. To combat these issues, PT. Pertamina EP Adera Field launched the Sustainable and Environmentally Friendly Agriculture program (PSRLB) in Desa Payu Putat, focusing on the Family Medicinal Plant and Organic Rice Cultivation (Bu Togar Panik) sub-unit. Bu Togar Panik's mission is to educate and support farmers in transitioning from conventional to organic farming methods, emphasizing the effective use of household waste as organic fertilizer. The program aspires to transform Desa Payu Putat into an organic agriculture hub, offering a diverse range of commodities and setting an example for other villages to harness natural and human resources for organic farming. Crops include organic rice and eight vegetable types: water spinach, long beans, basil, cherry tomatoes, purple eggplant, bird's eye chili, bok choy, and cucumbers. Additionally, nine Family Medicinal Plants (TOGA) varieties, such as red ginger, pineapples, galangal, sambang, and moringa leaves, are cultivated. Launched in 2022, the program in 2023 includes activities such as organic rice cultivation training, MOL and organic pesticide preparation training, herbal basic and advanced training, facility and infrastructure procurement, group management training, and land development. Bu Togar Panik has demonstrated positive outcomes, such as organic compost and MOL production, diverse organic crops, and the formation of local farmer groups.